Analisis Minat Baca Intensif Berbasis Cerita Rakyat Melalui Media Audiovisual pada Mahasiswa PBSI UIN Jakarta - Rini Andriani; Salma Jasmine Kamal; Husna Afifah; Syifa Fauziyah Rahma (Jurnal Pendidikan dan Sastra Inggris, 2024)
This research is motivated by the declining interest in reading in students which results in low knowledge of students. The theoretical foundations used in this research are reading interest theory, digital technology literacy theory, audio visual media theory and folklore theory. The method used is a qualitative approach using descriptive methods through interview techniques. The results of this study indicate that the use of folklore-based audio visual media can increase interest in intensive reading in Indonesian Language and Literature Education (PBSI) students from Syarif Hidayatullah State Islamic University Jakarta. In order for students to be more interested in listening and reading through the use of audio visual media downloaded from the YouTube application. This study aims to provide an in-depth insight into how the application of audiovisual media can affect the intensive reading interest of PBSI students from UIN Jakarta towards folklore, as well as provide a foundation for the improvement of learning strategies in this area.